Economic insecurity increases high earners’ preference for risk - Xiaoyan Wang; Lina Wang; Rong Huang; Yanping Qin; Ying Guo (BMC Psychology)
Abstract This study examines how economic insecurity and income level influence individuals’ preferences for risk in decision-making. Economic insecurity was experimentally manipulated in a laboratory setting, and participants’ risk preference was subsequently assessed using the Balloon Analogue Risk Task (BART). Participants completed the BART under either a gain frame, where inflating a virtual balloon increased potential monetary gains (Experiment 1), or a loss frame, where ballon inflation was necessary to avoid monetary loss (Experiment 2). Results showed that, in both gain and loss contexts, high-income individuals experiencing greater economic insecurity exhibited a higher preference for risk compared to those with lower economic insecurity, whereas no difference in risk preference was observed among low-income individuals (Experiment 1 and 2). Additionally, in the loss context, high-income participants manifested a greater preference for risk than low-income participants. Overall, the findings suggest that economic insecurity heightens risk preference among high earners.